ANALISIS TINGKAT KEDISIPLINAN SISWA AKIBAT PEMBERIAN SANKSI MATERIAL DI SMA NEGERI 1 BUKIT BATU KABUPATEN BENGKALIS - Kurniawati, Eni; Zahirman, Zahirman; Eddison, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research backgrounded by marks sense indisciplinary student and breaches school regulation. It because of student is still was aware just how the importance for to play the game whatever available. This research intent to know what available sanction application influence to student discipline at SMA Negeri 1 Bukit Batu Bengkalis's Regency. So writer takes research title â€œ Analisis Increases Effect Student discipline Sanction Application Significant at SMA Negeri 1 Bukit Batu Bengkalis's Regencyâ€. Formula in observational it is how increase effect student discipline sanction application significant at SMA Negeri 1 Bukit Batu Bengkalis's Regency?. To the effect this research is subject to be know how student discipline zoom sanction application effect significant at SMA Negeri 1 Bukit Batu Bengkalis's Regency. Population in observational it is exhaustive student at SMA Negeri 1 Bukit Batu Bengkalis's Regency that has once done new regulation beginning breach diberlakukan since January 2015 which is as much 173 person and total sample 43 person. Instrument is data collecting which is questionnaire consisting of 63 questions. Data analysed by Descriptive kualitatif passes through percentage. Of respondent answer percentage count as a whole acquired good answer as much 92,34% one lays in rank 76% 100%. Hypothesis thus that declares for to increase effect student discipline sanction application significant at SMA Negeri 1 Bukit Batu Regency Bengkalis is good, accepted.Â Key words: Student discipline, Sanction Significant